A extrafiscalidade ambiental como meio de efetivação do desenvolvimento sustentável - Santiago, Vanessa Aparecida Costa (2013)
The Federal Constitution, in its article 170, provides that the Economic Order is founded on free enterprise and human labor valuation, in order to ensure a dignified existence. The dignified existence is linked to quality life, on the other hand, it¿s intrinsically related to the way the company absorbs and transforms its resources, ie, combine balance in the distribution of income and living healthier, which in turn comes against the scarcity of natural resources and compromising the environment, sustainable development. The sustainability appears in this regard as the source of equilibrium, exploitation of natural resources going to happen so that resources are maintained, without disregarding the social satisfaction generated by the activity economic, which is guaranteed by article 225 of the Federal Constitution. The preservation of ecologically balanced environment as a duty of State, resulting in its Duty/Power of developing public policies aimed at environmental balance within a sustainable development perspective. Sustainable development seeks precisely harmonize the imbalance between economic development and environment preservation, but this requires that the environment externalities are internalized, the ideal is to get a market price that incorporates each fraction of resource used, following the Principle of Polluter Payer. However, it is known that the tax policy is an effective instrument of public management in the induction of behavioral socioeconomic status. Regarding to the environment, the possibility of using the tax as an instrument of its protection is directly related to the application of extra tax technique that may be applied in all kinds of taxes. Brazil already applies to extra tax technique in several taxes. In Comparative Law it was found that the European Union and North America uses much more of extra tax technique on their function and adopts the so-called Green Tax Reform to improve the instrument. Even comparing to the Mercosur countries, Brazil has highlighted the applicability of the Environmental extra tax technique. Presented on the work of the new paths extra tax technique in Brazil using the PEC 353/2009 as a source of this note, and was presented some suggestions for each tributary species and the end addressed practice of tax incentives as effective as the extra tax instrument of environmental protection.